Digitalization of Media Create Precocious Alpha Generation - Ari Susanti (Jurnal Spektrum Komunikasi, 2023)
Alpha generation is born after 2010. They grew up and live with sophisticated digital technology. They are used to operating modern technology in daily activities. They are used to using technology to communicate with others, in the real world and the virtual world. Many public spheres in cyberspaces have been explored by them such as YouTuber, TikTok, WhatsApp, Facebook, online game, online news, e-commerce, m-banking and so on. This technology is called a smartphone which provides various conveniences with information services and unlimited benefits. This causes the alpha generation to enjoy the virtual world and ignore their activities in the real world. The lack of censorship on content uploaded in cyberspace makes the mindset and behavior of the alpha generation, who are still unstable, forced to mature and mature before their age. So that the digitization of this media can trigger a premature alpha generation. Various anticipations have been created by technology, for example applications that can filter content that is not suitable for children such as adult content, violence, issues of intolerance, and others. However, this protection is not enough. The role of parents is very important to overcoming this problem. Children spend more of their free time at home. Full support and concern from the government, society, academia and the media will complement various efforts to make the alpha generation free from digital fantasy addiction.